To history of labarotory of forest soil sciences at URIFFM A. S. Skorodumov, naval officer and researcher - Vergunov, V. A.; Migunova, Ye. S. (Forestry and Forest Melioration, 2019)
Early stages of the development of soil sciences at URIFFM are given in brief. The article contains materials on almost completely forgotten scientific activities of one of the greatest forest soil researchers Aleksandr S. Skorodumov who had worked in URIFFM for about 20 years. And then, for nearly the same period of time, he was involved in developing measures on land erosion control at the Educational and Scientific Centre the Institute of Agriculture of NAAS. Forest-type soil evaluation for several natural zones and studies on how artificial stands influence soils in arid steppes were among his works. The subject of his last research was southern blacksoils in former Volodymyrska Agroforestry Experimental Station in URIFFM (Mykolayiv Region). Later on, when working at the Institute of Agriculture, he defended his Doctoral thesis in Moscow University in these areas and became Dr Hab in Biological Sciences. Then he obtained an academic rank of Prof. Dr. At that Skorodumov had served in the navy for 12 years. Some other facts given in the article show that there are no sufficient materials or objectivity in history of URIFFM. 4 Figs., 20 Refs.